Population Genetic Structure And Breeding Pattern Of The Yellow Fever Mosquito Aedes Aegypti Subspecies With Emphasis On Their Disease Transmission In Sudan - Abuelmaali Elamin, Sara Abdelrahman (2022)
The current study investigated the distribution, genetic diversity, and structure, and virus transmission for eight populations of the two Aedes aegypti subspecies Aedes aegypti aegypti (Aaa) and Aedes aegypti formosus (Aaf) in Sudan's Sahelian region. The distribution and genetic variations of the two subspecies in different parts of Sudan were explored using two mitochondrial markers (CO1 & ND4). Using seven microsatellite markers, the population structure, and phylogenetic relationships were investigated in their various geographical areas. Flavivirus and Alphavirus viruses were examined in Ae. aegypti. The results revealed that both Ae. aegypti subspecies are found in the Sahelian belt, Aaa and distribution was found in four study sites east of the Nile River named by Port Sudan, Kassala, Tokar and Barakat then Aaf distributed in the other four sites west of the Nile River named by Kadugli, Al Junaynah, Al Fasher and Nyala. The CO1 and ND4 mitochondrial genes demonstrated low gene flow and considerable genetic variability between the two subspecies.